CREATIVE ECONOMIC DEVELOPMENT MODEL THROUGH INCREASED INNOVATION AND PERFORMANCE AND ITS IMPACT ON COMPETITIVENESS IN SOUTH BANGKA DISTRICT: MODEL PENGEMBANGAN EKONOMI KREATIF MELALUI PENINGKATAN INOVASI DAN KINERJA SERTA DAMPAKNYA TERHADAP DAYA SAING DI KABUPATEN BANGKA SELATAN - Reniati; Meidarina Yunfin; Hamsani (Universitas Lambung Mangkurat, 2024)
This study is a creative economy development model through increasing innovation and performance and its impact on competitiveness in South Bangka Regency which aims to analyze the influence of creativity, competence, government access (capital), infrastructure and competitiveness on innovation and creative economy performance, analyze the influence of innovation on creative economy performance, and the influence of performance on competitiveness using quantitative methods with a sample of 95 creative economy actors in South Bangka Regency. The multivariate analysis used in this study is Structural Equation Modeling with the Partial Least Square (SEM-PLS) technique.. The results of the analysis show that the creativity variable has an indirect influence on competitiveness through the performance variable. The infrastructure and market access variables also have an indirect influence on the variables through the performance variable, as well as indirectly on competitiveness through the innovation and performance variables.